El destino de las almas tiránicas = The fate of tyrannical souls (2017)
The ethical question of the good life in ancient philosophy was always linked to the public behavior of life in the polis. to the public behavior of life in the polis. In this article, the fate of tyrannical souls according to Plato and Xenophon the fate to be expected by tyrannical souls according to Plato and Xenophon. After a brief historical historical context of the emergence of the figure of the tyrant in Greek political life, the discussion of the Greek political life, the discussion that Socrates engages in the Gorgias with the sophists about the tyrant is the sophists on the tyrant, connecting his political exercise with the problem of virtue. of virtue. Thus, justice appears as an evaluative criterion of excessive behavior, hybridity of the tyrant's excessive behavior, of the tyrant's hybris. It is on this basis that the judgment of the tyrannical soul's the unhappiness of the tyrannical soul that appears in the Republic, shared by Xenophon in his Hieron, accompanied by in his Hieronymus, accompanied by a conclusion